pH-Dependent conformational changes in proteins and their effect on experimental pK(a)s: the case of Nitrophorin 4. - Natali V Di Russo; Dario A Estrin; Marcelo A Martí; Adrian E Roitberg (PLoS Computational Biology)
The acid-base behavior of amino acids is an important subject of study due to their prominent role in enzyme catalysis, substrate binding and protein structure. Due to interactions with the protein environment, their pK(a)s can be shifted from their solution values and, if a protein has two stable conformations, it is possible for a residue to have different "microscopic", conformation-dependent pK(a) values. In those cases, interpretation of experimental measurements of the pK(a) is complicated by the coupling between pH, protonation state and protein conformation. We explored these issues using Nitrophorin 4 (NP4), a protein that releases NO in a pH sensitive manner. At pH 5.5 NP4 is in a closed conformation where NO is tightly bound, while at pH 7.5 Asp30 becomes deprotonated, causing the conformation to change to an open state from which NO can easily escape. Using constant pH molecular dynamics we found two distinct microscopic Asp30 pK(a)s: 8.5 in the closed structure and 4.3 in the open structure. Using a four-state model, we then related the obtained microscopic values to the experimentally observed "apparent" pK(a), obtaining a value of 6.5, in excellent agreement with experimental data. This value must be interpreted as the pH at which the closed to open population transition takes place. More generally, our results show that it is possible to relate microscopic structure dependent pKa values to experimentally observed ensemble dependent apparent pK(a)s and that the insight gained in the relatively simple case of NP4 can be useful in several more complex cases involving a pH dependent transition, of great biochemical interest.